Diagnosis and surgical outcomes of coarctation of the aorta in pediatric patients: a retrospective study - Gong, Ting; Zhang, Feiyan; Feng, Lingxin; Zhu, Xu; Deng, Dan; Ran, Tingting; Li, Liling; Kong, Li; Sun, Liqun; Ji, Xiaojuan (Frontiers in Cardiovascular Medicine, 2023)
Background Coarctation of the aorta (CoA) is a common congenital cardiovascular malformation, and improvements in the diagnostic process for surgical decision-making are important. We sought to compare the diagnostic accuracy of transthoracic echocardiography (TTE) with computed tomographic angiography (CTA) to diagnose CoA. Methods We retrospectively reviewed 197 cases of CoA diagnosed by TTE and CTA and confirmed at surgery from July 2009 to August 2019. Results The surgical findings confirmed that 19 patients (9.6%) had isolated CoA and 178 (90.4%) had CoA combined with other congenital cardiovascular malformations. The diagnostic accuracy of CoA by CTA was significantly higher than that of TTE (χ2 = 6.52, p = 0.01). In contrast, the diagnostic accuracy of TTE for associated cardiovascular malformations of CoA was significantly higher than that of CTA (χ2 = 15.36, p < 0.0001). Infants and young children had more preductal type of CoA, and PDA was the most frequent cardiovascular lesion associated with CoA. The pressure gradient was significantly decreased after the first operation, similar at 6 months, 1 year, and 3 years follow-ups by TTE. Conclusions CTA is more accurate as a clinical tool for diagnosing CoA; however, TTE with color Doppler can better identify associated congenital cardiovascular malformations. Therefore, combining TTE and CTA would benefit clinical evaluation and management in patients suspected of CoA. TTE was valuable for post-operation follow-up and clinical management.